Analisis Tingkat Kepuasan Nasabah Dengan Pendekatan Fuzzy Logic Dalam Upaya Peningkatan Kualitas Pelayanan (Studi Kasus Cujk Batuaji ) - Ndoya, Yohana; Putri, Anggia Dasa (LPPM Universitas Putera Batam, 2024)
This research aims to analyze the level of customer satisfaction of CUJK Batuaji using the Fuzzy Logic approach, focusing on four main variables: service quality, product quality, price quality, and atmosphere quality. The Fuzzy Logic approach was chosen because of its flexibility in handling uncertain and ambiguous data, as well as its ability to provide a more accurate picture of customer satisfaction levels. Data is collected through surveys filled out by customers, with each variable assessed on a scale of 1 to 5. The assessment results are converted into fuzzy values and analyzed using predefined fuzzy rules. The inference process was carried out using the Mamdani method, and the final results were defuzzified to obtain a representative crisp value. The research results showed that: Service quality received a score of 78.65, which is in the